Development of Class XIII Fiqh Learning Videos in MTs Al-Ghafur Payudan Karangsokon Guluk-Guluk Sumenep - Faiqatul Munawwarah; Nurul Zainab (Kasyafa: Jurnal Pendidikan Agama Islam, 2024)
Grade VIII students at MTs Al-Ghafur have low comprehension skills. After being analysed, the cause is because the teaching materials used are not in accordance with the needs of students. The purpose of this study is to develop ICT-based PAI teaching materials according to the needs of students so that there is an increase in their interest in learning and increase their understanding.  The teaching materials to be developed in this study are based on learning videos on the Jurisprudence material of the Grant chapter. This type of research uses the Riseacrh and Development (R&D) approach. This research and development procedure uses the ADDIE model. Data collection techniques use qualitative descriptive validation which will ultimately describe the results of teaching materials. Data collected through instruments during the trial were analysed using statistics. The results of this study indicate that teaching materials with this learning video are very feasible to use. Judging from the results of validation conducted by experts 87.5% and from the results of student responses 96.67%. So the learning video developed in class VIII is effective for increasing student interest in learning so that it encourages increased student understanding. It can be concluded that learning video teaching materials can be used according to student needs.